Rotina de alto nível em uma empresa líder da indústria do ônibus : um estudo ostensivo e performativo a partir das teorias da firma, evolucionária e posicionamento competitivo - Silva, Oberdan Teles da (My University, 2018)
The thesis presents a conceptual framework based on the theory of the firm, it is focused on organizational evolution and competitive positioning and it is based on routines and strategy constructs. The research was conducted with such theorical context and deals with high-level quality routine in the company Beta SA, one of the leading bus manufacturers of the world, headquartered in the State of Rio Grande do Sul, Brazil. The conceptual framework considered ostensible and performative aspects of the research, which included an interactionist methodological individualist strategy and the elements of the evolutionary, such as variation, selection and retention. The routine study is characterized as a qualitative approach, with a descriptive objective, having as a research strategy a single case study. The techniques were semi-structured interviews, using thematic oral history, projective technique and documentary analysis. From the variation constructs, arising from the routine and the evolutionary theory, 42 questions were identified from various characteristics, such as rational selection, blind selection, selective propagation, path dependence, imitation, endogenous variation, micro-change, patterns, tacit and explicit knowledge, emerging and repertoire. These characteristics were investigated from a selection perspective, using the theories of the firm and of competitive positioning. The concept of retention is dealt with the elements that extend the competitive scope of the routine and limitation in which they are restrained. Ten coordinators, from the operational level, 09 managers of the tactical level and 10 directors of the strategic level participated in the research. The analysis occurred individually and then each analysis was compared with the corresponding level. At the end of the analysis of each of the constructs, inference systems were formed to correspond to the symmetrical responses, where the dispersion systems corresponding to the asymmetries of conception and the quality routine of Beta S.A. The whole interviews procedure allowed the identification of 34 inference systems at the operational level, 42 inference systems at the tactical level and 39 inference systems at the strategic level. For each unit, a cause and effect relationship was established, by comparing them with the empirical model of the organisation. Relationships of the limiting factors and potentiates of the routine from sub-levels were also structured. The results show that the evolution of the routine is due to interactions, errors and customization. It was also established that the endogenous evolution of the routine results from the recognition of the restriction and the emphasis on prevention. In the routine learning process, the results indicated the need to systematize the tacit knowledge into internal and greater routine communication. The study demonstrated the empirical similarity with the theoretical concepts of regularity of the routines, the different interpretations, the patterns of heterogeneous operation and the discovery practices. In the performative aspect, two models were designed to enhance the quality routine of Beta S.A. The first is the structure of the future strategies conditioned to the study of retrospective variations, interactions and learning. The second was designed to increase the absorption capacity of the quality decision-making committee through the individual transforming knowledge from single to double loop.
A tese apresenta quadro conceitual baseado nas teorias da firma, evolucionária e posicionamento competitivo. É formado pelos construtos rotina e estratégia onde pesquisou-se a evolução da rotina de alto nível, representada pela qualidade da empresa Beta S.A., uma das maiores encarroçadoras de ônibus do mundo, com matriz no Rio Grande do Sul. O quadro é constituído pelos aspectos ostensivo e performativo, pelo individualismo metodológico interacionista e pelos elementos evolucionários: variação, seleção e retenção. O estudo caracterizou-se como uma abordagem qualitativa, com objetivo descritivo, tendo como estratégia de pesquisa estudo de caso. As técnicas de coleta foram a entrevista semiestruturada, história oral temática, técnica projetiva e pesquisa documental. Na variação, decorrentes da teoria evolucionária e do construto rotina, considerou-se para análise 42 questões divididas entre os blocos: seleção racional, cega, propagação seletiva path dependence, imitação, variação endógena, micromudança, padrões, conhecimento tácito e explícito, fatores emergentes e repertório individual. Pesquisaram-se os blocos, a partir da seleção, por meio das teorias do crescimento da firma e do posicionamento competitivo. Na retenção, consideraram-se os elementos que ampliam o escopo competitivo da rotina e que a limitam. Participaram da pesquisa 10 coordenadores, representados pelo nível operacional, 09 gerentes do nível tático e 10 diretores do nível estratégico. A análise ocorreu individualmente e após comparou-se com o nível correspondente. Ao final da análise de cada um dos blocos, formavam-se sistemas de inferência, que correspondiam as respostas simétricas, onde se caracterizavam, na sequência, os sistemas de dispersão, que correspondiam as assimetrias de concepção quanto a rotina da qualidade da Beta S.A. No nível operacional identificaram-se 34 sistemas de inferência, 42 no tático e 39 no estratégico. Em cada um dos blocos estabeleceram-se relações de causa e efeito comparados no modelo empírico da organização. Também se estruturaram, relações dos fatores limitantes e potencializadores da rotina a partir de subníveis. Evidenciou-se que a evolução da rotina, se deu pelas interações, erros e customização. Também se constatou que a evolução endógena da rotina, decorre de reconhecimento da restrição e ênfase na prevenção. Na aprendizagem da rotina, os resultados indicaram a necessidade de sistematização do conhecimento tácito em processo e maior comunicação. O estudo demonstrou simetria empírica com os conceitos teóricos de regularidade das rotinas, interpretações distintas, padrões heterogêneos e práticas de descobrimento. No aspecto performativo estruturou-se dois modelos para potencializar a rotina da qualidade da Beta S.A. Um, é a estruturação de estratégias futuras condicionadas ao estudo das variações retrospectivas, interações e aprendizagem. O outro objetiva ampliar a capacidade de absorção do comitê decisor da qualidade por meio do indivíduo e de segmentação de mercados transformando conhecimento de laço simples em duplo.
Keywords: Administração de empresas; Controle de qualidade; Produtividade do trabalho; Ônibus; Industrial management; Quality control; Labor productivity; Buses